Discovery of Lijianmin-Chengkun Complexes and Their Oncological Application in Osseous and Intraarticular Lesions Around the Knee - Shao, Xianhao; Li, Jianmin; Zhang, Ailin; Yao, Yuan; Sun, Feifei; Li, Zhenzhong; Liu, Tao; Hou, Haiqing; Li, Qiuyao; Li, Zhenfeng; Gao, Xiaofei; Yang, Qiang; et al. (Frontiers in Surgery, 2021)
Objective: This research aims to refresh the limited understanding about the canal and vascular structures within the epiphysis and metaphysis of the tibia and femur and their oncological significance. Methods: This study was started with characterization of a novel structure using radiographs and anatomic dissections, followed by a descriptive clinical study with 55 participants to investigate the effects of tumors on this novel discovery and a retrospective cohort study with 82 participants to investigate whether the structure would be a risk factor for tumor recurrence after the curettage of giant cell tumor of bone. Results: A new anatomical knee structure, the Lijianmin-Chengkun (LC) complex, was discovered in healthy adults, and its clinical implications were examined in this study. This new-found anatomical structure is composed of an epiphyseal and metaphyseal canal which surrounds a blood vessel, foramen, and foramen-covered synovium. All LC complexes showed similar radiographical, anatomical, and histological characteristics and were located within specific tibial and femoral intercondylar regions. These LC complexes seem to facilitate tumor residue and extension and may be a risk factor for tumor recurrence after curettage of femoral and tibial giant cell tumors (P=0.031). Conclusion: The LC complexes are related to local tumor recurrence and bidirectional tumor dissemination between intraosseous and intraarticular regions. These findings have opened up a new perspective and may provide new targets for intervention in malignant and aggressive tumors around the knee joint.